Experimental study of the heat transfer of single-jet impingement cooling onto a large heated plate near industrial conditions. (March 2022) - Oliveira, A. V. S.; Maréchal, D.; Borean, J.-L.; Schick, V.; Teixeira, J.; Denis, S.; Gradeck, M.
Highlights: Jet impingement cooling for different Reynolds numbers, from 9, 800 to 120, 000. Results of the dissipated heat, transverse heat flux, and rewetting and maximum cooling rate fronts. Large-scale tests provide important data of the cooling, in particular far from the impact location. Similar results for different jet nozzle diameters but with the same flow rate. The higher the Reynolds number, the larger the heat dissipation far from the impact location. Abstract: Jet impingement cooling has been intensively studied in the past by many authors because of its important application in the metallurgical industry; however, most of the experiments in the literature are at laboratory scale and, in some cases, not near industrial conditions. In this study, we performed cooling experiments near industrial conditions in a new experimental apparatus with a large nickel plate as test sample, which was heated until 850  ∘ C before being cooled by a single circular water jet. Five experimental results are presented with different jet Reynolds numbers, from 9, 800 to 120, 000, obtained by varying the water flow rate and the nozzle diameter. The presented results are: temperature evolutions during cooling, dissipated heat flux (estimated by solving a 2D inverse heat conduction problem), transverse heat flux at the heat-exchanging surface, and the characteristics (position and velocity) of the rewetting and maximum cooling rate fronts. The increase in the jet Reynolds number increased slightly the heat flux at the stagnation zone, but increased it substantially for positions farther from the impact location. The transverse heat flux increased with the passage of the rewetting front and then decreased, and its magnitude was practically the same regardless of the jet Reynolds number. The change in the nozzle diameter did not affect significantly the heat transfer nor the rewetting front growth, although the heat dissipation was slightly higher with the smaller nozzle, possibly because of the higher jet impact velocity. Finally, we compared the present results with some found in the literature in similar conditions, showing that laboratory experiments are valuable to provide detailed information, especially near the stagnation zone, but large-scale experiments allow obtaining macroscale data of the cooling process.